Compliance Intention to Pay Zakat on Salary - Najwa Mohd Khalil; Hanudin Amin; Nur Shahirah Azman (Center of Strategic Studies (PUSKAS) BAZNAS, 2020)
ABSTRACT This study examines the effects of attitude, subjective norm, perceived behavioural control and taqwa on compliance intention to pay zakat on salary in East Malaysia. A deductive approach is employed to examine young public servants' compliance intention to contribute to zakat payment on their salary. The model is tested using survey data from 202 respondents in Kota Kinabalu, Sabah, East Malaysia. The results obtained indicate that attitude, subjective norm and perceived behavioural control are significantly related to the compliance intention. Besides these factors, taqwa is also significant. Besides, the post hoc analysis indicates that attitude can play a role as a mediating variable for the relationship between taqwa and compliance intention. This study improves the generalisation of the theory of planned behaviour (TPB) to include zakat payment, where Islamic altruism is brought into play. Our findings are of the essence to provide valuable insights for zakat authority to manage zakat payers effectively by considering new millenials as new zakat payers' base and patronage factors as captured in this study